Female consumer awareness on difference between original & fake Halal logo JAKIM on product : a study on female muslim consumer in University Malaysia Pahang - Nor Amira , Azahar (2014)
Recognizing today‘s women are the biggest contributors as consumers of various products around the world and the high demand for halal food in Malaysia and the world in general, there are the government's efforts to position Malaysia as a regional hub for halal food products. However, there are circumstances where female users do not really understand what exactly halal. This is due to low awareness among women consumers about halal food, halal logo and all associated with halal. Moreover, it is because of lack of knowledge or information about the cause halal meaning misunderstood the true meaning of halal. Therefore, this study was conducted to determine the user's perception of Muslim women bearing the halal food. In addition, this study also aims to identify consumer awareness of Muslim women related factors emphasized in the selection of food and the importance of choosing the logo halal food. A total of 300 respondents among students and employees at Universiti Malaysia Pahang has been involved in this study. Set questionnaire containing 28 items were distributed to the respondents and analyzed descriptively to obtain the frequency, percentage and min using Statistical Package for Social Science (SPSS) version 2.0. Data were analyzed using Cronbach Alpha, Test-T, Reliability Analysis, Correlation and Analysis Reg'resi.Analisis data shown in tables. Overall results showed that respondents gave a positive perception of aspects studied. The ﬁndings show that consumer awareness of the halal logo with a mean value of 4.2244. While the mean of the factors emphasized in dietary knowledge is highest with a mean of 4.2542 and the mean for halal food security is 4.1789. At the end of the study, the researchers made several recommendations to the parties to be aware of the problem studied. Further studies were also proposed for research in the future